Continuous flow photolysis of aryl azides: Preparation of 3H-azepinones - Bou-Hamdan, Farhan R.; Lévesque, François; O'Brien, Alexander G.; Seeberger, Peter H. (Beilstein Journal of Organic Chemistry, 2011)
Photolysis of aryl azides to give nitrenes, and their subsequent rearrangement in the presence of water to give 3H-azepinones, is performed in continuous flow in a photoreactor constructed of fluorinated ethylene polymer (FEP) tubing. Fine tuning of the reaction conditions using the flow reactor allowed minimization of secondary photochemical reactions.
Keywords: azepinones; azides; continuous flow; nitrenes; photochemistry